Hypercalcaemia‐induced kidney injury caused by the vitamin D analogue calcitriol for psoriasis: a note of caution when prescribing topical treatment. (1st December 2016) - Corden, E.; Higgins, E.; Smith, C.
Summary: A 55‐year‐old man with severe plaque psoriasis presented with a 2‐week history of feeling generally unwell with lethargy and thirst. His symptoms had developed 6 weeks after commencement of the topical vitamin D3 analogue calcitriol. Investigations revealed hypercalcaemia and acute‐on‐chronic kidney injury, probably directly induced by systemic absorption of vitamin D3 following extensive topical use. Topical calcitriol had been started as a steroid‐sparing agent to reduce the patient's liberal potent corticosteroid usage during anti‐tumour necrosis factor‐alfa therapy. Topical vitamin D analogues are commonly prescribed in dermatological and general practice, with hypercalcaemia being a rare but potentially serious adverse effect. This case serves to outline key factors that may predispose to hypercalcaemia, such as disease extent, quantity of drug applied, comorbidities and concurrent medications, and it highlights the importance of considering these factors when prescribing topical therapies.